Учні А.П Ковалівського: Ю.Г. Литвиненко - Чувпило, О.О. (Хазарский альманах, 2005)
В статье освещается жизнь и научное наследие Ю.Г. Литвиненко (1929-1990) -одного из ведущих украинских индологов, ученика выдающегося ориенталиста А.П. Ковалевскго. Научное наследие Ю.Г Литвинвнко условно разделено на четыре рубрики; 1) труды по истории рабочего движения в Британской Индии; 2) сочинения гю истории индийского коммунистического движения; 3) работы по истории национально-освободительного движения народов Индии: 4) индологические публикации в Украинской советской энциклопедии. Автор пришел к выводу, что хотя Ю.Г Литвиненко и не выдвинул фундаментальных концепций истории индийского рабочего и национально-освободительного движения, внес посильный вклад в становление и развитие украинской индологии. The life and scientific heritage of one of thB leading Ukrainian indologist, a disciple of the prominent orientalist A.P. Kovalevsky, Yu.G. Litvinenko (1929-1990). There are studied in the article Yu.G. Litvinenko’s scientific heritage is conditionally divided into four parts: 1) works from the history of the labour movement in the British India; 2) essays on the history of Indian communist movement; 3) studies on the history of national liberation movement of Indian peoples; 4) indological publications in the Ukrainian Soviet Encyclopedia. The author concluded that though Yu.G. Litvinenko has not promoted any fundamental conception of the history of the Indian labour and national liberation movement he had made certain contributions in rise and development of Ukrainian indology.